Comparative assessment of several automatic CPAP devices' responses: a bench test study - Valentina Isetta; Daniel Navajas; Josep M. Montserrat; Ramon Farré (ERJ Open Research, 2015)
Automatic continuous positive airway pressure (APAP) devices adjust the delivered pressure based on the breathing patterns of the patient and, accordingly, they may be more suitable for patients who have a variety of pressure demands during sleep based on factors such as body posture, sleep stage or variability between nights. Devices from different manufacturers incorporate distinct algorithms and may therefore respond differently when subjected to the same disturbed breathing pattern. Our objective was to assess the response of several currently available APAP devices in a bench test. A computer-controlled model mimicking the breathing pattern of a patient with obstructive sleep apnoea (OSA) was connected to different APAP devices for 2-h tests during which flow and pressure readings were recorded. Devices tested were AirSense 10 (ResMed), Dreamstar (Sefam), Icon (Fisher & Paykel), Resmart (BMC), Somnobalance (Weinmann), System One (Respironics) and XT-Auto (Apex). Each device was tested twice. The response of each device was considerably different. Whereas some devices were able to normalise breathing, in some cases exceeding the required pressure, other devices did not eliminate disturbed breathing events (mainly prolonged flow limitation). Mean and maximum pressures ranged 7.3–14.6 cmH2O and 10.4–17.9 cmH2O, respectively, and the time to reach maximum pressure varied from 4.4 to 96.0 min. Each APAP device uses a proprietary algorithm and, therefore, the response to a bench simulation of OSA varied significantly. This must be taken into account for nasal pressure treatment of OSA patients and when comparing results from clinical trials.